Estudio de factibilidad para la creación de una planta productora, procesamiento y comercialización de pavos en el cantón Bolívar - Delgado Burgos, Juan Manuel (2015)
The purpose of this project was to develop a feasibility study for the creation of a new plant for the production, processing and marketing of turkeys in the canton of the Bolivar province of Manabi-Ecuador; For which in the first phase of implementation is conducted a market study to see what is on offer and the demand for the product in the city, performing a survey of the economically active population of the canton Bolívar, the same that consisted of eleven questions closed and that we got as a result the acceptance of the turkey meat in this canton. In the second phase was carried out a technical diagnostics to check the feasibility of this project, in which it was determined the size of the plant, as well as its location, distribution of the plant, its administration, suppliers, machinery use, workers, description of processes and products. In the third phase a study gender economic-financial in where it was determined the costs generated in this project, for which we used several accounting methods, among them, the cost-benefit analysis of, where it was determined the point of balance, recovery of capital as well as was also used the formulas to calculate the IRR and NPV to verify if the investment is feasible and It will be accepted by investors. He also did a SWOT matrix that served to analyze the environment in which they are going to sell the product, whether these external and internal factors, at the end it was found that the project is feasible, and that will help the economy of the sector and to the diversity of the people food.